A new species of the genus Thalassironus (Nematoda: Enoplida: Ironidae) from the coasts of South Korea - Jeong, Raehyuk; Tchesunov, Alexei V.; Lee, Wonchoel (Zootaxa, 2019)
A new species of the genus Thalassironus de Man, 1889 was discovered during several surveys of the offshore marine ecosystem in Korea. This new species belonging to the family Ironidae, Thalassironus koreanus sp. nov., shares general morphological traits of the genus such as an optically smooth cuticle, buccal cavity consisting of two parts with three movable teeth and thick cuticularized walls, six rounded lips with ten cephalic setae, slit-like amphid and short conical tail with caudal glands present. The new species is most closely related to T. bohaiensis, first discovered in the Bohai Sea, in terms of body ratio (a, b, c, c’) and general morphology, but differs by its generally longer and larger body structures, cervical setae at the level of the buccal cavity, paired somatic setae distributed along the body, and longer/larger spicule. A description of Thalassironus koreanus sp. nov., diagnosis of the genus, emended pictorial key for the genus and discussion of important characteristics for the genus is provided.